Оздоблення кінських вуздечок з кургану Товста Могила: пошук закономірностей - Полідович, Ю.Б. (Археологія і давня історія України, 2021)
У статті аналізується оздоблення вуздечок коней, похованих у двох кінських могилах (Північній і Південній) у кургані Товста Могила. На основі аналізу пропонується реконструкція певних уявлень скіфів про потойбіччя, шлях до Світу предків та його фінальний етап — прибуття до богині, яка зустрічала душі померлих. The paper is devoted to the analysis of horse bridles from Tovsta Mohyla kurgan of the 4th century BC. The barrow was excavated by the expedition of Ukrainian Institute of Archaeology headed by Boris Mozolevsky in the Dnepropetrovsk oblast, Ukraine, in 1971. In this kurgan the burial of noble warrior and two horse graves with skeletons of 6 horses were found. The horses had bridles decorated with images of various animals and fantastic creatures. One bridle was decorated with the images of mythological characters: the serpentine goddess (Rankenfrau, probable Scythian goddess Api) and two Scythian gods who were portrayed as the Greek gods Hercules and Dionysus. All bridles have analogies in other Scythian assemblages of the 4th century BC. It has been suggested that the reproduction of certain images is associated with ideas about the path of the deceased to the Ancestor’s World. The bridles were decorated with images of fantastic animals and were a kind of mask. According to the Scythian beliefs such a bridle-mask helped to endow the horse with special properties so that it could overcome obstacles on the way to the Ancestor’s World. Probably, the serpentine goddess (Rankenfrau) was the mistress of this Ancestor’s World. On the way to the Ancestor’s World the noble warrior was accompanied by his assistant, marked by archaeologists as «groom No. 3». Such a scene is depicted in the crypt of Anfesterii from Panticapaeum on the Bosporus (modern Kerch, Crimea). It depicts the arrival of the deceased on horseback, accompanied by assistant, to the goddess, mistress of the Ancestor’s World. Further research on this topic will extend our understanding of the Scythian ideas about the Beyond.